2005
DOI: 10.1007/s10802-005-6734-7
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Temperament and Family Environment as Predictors of Internalizing and Externalizing Trajectories From Ages 5 to 17

Abstract: Childhood temperament and family environment have been shown to predict internalizing and externalizing behavior; however, less is known about how temperament and family environment interact to predict changes in problem behavior. We conducted latent growth curve modeling on a sample assessed at ages 5, 7, 10, 14, and 17 (N = 337). Externalizing behavior decreased over time for both sexes, and internalizing behavior increased over time for girls only. Two childhood variables (fear/shyness and maternal depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

45
391
14
18

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 449 publications
(489 citation statements)
references
References 79 publications
45
391
14
18
Order By: Relevance
“…Support for the differential susceptibility model was found in four studies Burk et al, 2011;Leve et al, 2005;Rioux et al, 2016), all assessing reactivity measures of temperament. In those studies, in addition to higher levels of externalizing behaviors or alcohol use in adverse family environments, more impulsive and disinhibited children as well as those low in fearfulness/shyness had lower levels of externalizing behaviors and alcohol use in positive family environments or in the absence of adversity compared to children lower in impulsivity and disinhibition and higher in fearfulness/ shyness.…”
Section: Support For the Differential Susceptibility Model And Implicmentioning
confidence: 85%
See 4 more Smart Citations
“…Support for the differential susceptibility model was found in four studies Burk et al, 2011;Leve et al, 2005;Rioux et al, 2016), all assessing reactivity measures of temperament. In those studies, in addition to higher levels of externalizing behaviors or alcohol use in adverse family environments, more impulsive and disinhibited children as well as those low in fearfulness/shyness had lower levels of externalizing behaviors and alcohol use in positive family environments or in the absence of adversity compared to children lower in impulsivity and disinhibition and higher in fearfulness/ shyness.…”
Section: Support For the Differential Susceptibility Model And Implicmentioning
confidence: 85%
“…Two studies assessed overarching temperament profiles and found significant interaction effects (Wills et al, 2001;Windle, 1992). Six of the ten studies assessing reactivity measures found significant interactions Burk et al, 2011;Leve et al, 2005;Rioux et al, 2016;Stice & Gonzales, 1998), with four of the six studies showing a further moderating effect of sex Burk et al, 2011;Leve et al, 2005;. Results for self-regulatory measures of temperament were consistent, although based on only a few studies.…”
Section: Interactions Between Temperament and The Family Environmentmentioning
confidence: 88%
See 3 more Smart Citations